2012
DOI: 10.1007/s00122-012-1878-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic components and major QTL confer resistance to bean pyralid (Lamprosema indicata Fabricius) under multiple environments in four RIL populations of soybean

Abstract: Bean pyralid (BP; Lamprosema indicata Fabricius) is one of the major leaf-feeding insects that affect soybean crops in central and southern China. Four recombinant inbred line populations (KY, WT, XG and SX) were tested during 2004-2006 in Nanjing, China, to identify quantitative trait loci (QTL) for resistance to BP on the basis of data for rolled leaflet percentage under field infestation conditions. The mapping was performed using QTL Network V2.0 and checked with Windows QTL Cartographer V2.5 and IciMappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…The general MCIM model incorporated the fixed terms of additive effects (A) and additive 9 additive epistatic effects (AA) as well as random terms for the environment, additive 9 environment interactions, and epistasis 9 environment interaction effects; in addition, the critical F value of the MCIM model was calculated with 10,000 permutation tests. The QTL effects were estimated using the Markov chain Monte Carlo method with 20,000 Gibbs sampler iterations and candidate interval selection and putative QTL detection, and the QTL effects were calculated with an experiment-wise type I error under a = 0.001 (Wang et al 1994;Yang et al 2007;Xing et al 2012). In this study, we analyzed the protein concentration data from all 20 environments.…”
Section: Qtl Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…The general MCIM model incorporated the fixed terms of additive effects (A) and additive 9 additive epistatic effects (AA) as well as random terms for the environment, additive 9 environment interactions, and epistasis 9 environment interaction effects; in addition, the critical F value of the MCIM model was calculated with 10,000 permutation tests. The QTL effects were estimated using the Markov chain Monte Carlo method with 20,000 Gibbs sampler iterations and candidate interval selection and putative QTL detection, and the QTL effects were calculated with an experiment-wise type I error under a = 0.001 (Wang et al 1994;Yang et al 2007;Xing et al 2012). In this study, we analyzed the protein concentration data from all 20 environments.…”
Section: Qtl Mappingmentioning
confidence: 99%
“…The identification of genes/QTLs and the development of higher-density molecular genetic maps have facilitated the study of complex quantitative traits, and the analysis of genes has resolved the related traits into individual Mendelian factors (Xing et al 2012). Highdensity or integrated genetic linkage maps of soybean have been constructed by Cregan et al (1999), Song et al (2004), Choi et al (2007), Hyten et al (2010a, b) and Qi et al (2014a, b).…”
Section: Introductionmentioning
confidence: 99%
“…QTLs associated with complex abiotic and biotic stresses tolerance traits have been targeted and elucidated their relations with other traits by several approaches (www.phytozome.net/soybean; http://soybase.org). A number of QTLs for abiotic and biotic stresses as well as flowering/maturity have been identified using several populations across environments (Abdel-Haleem et al, 2012;Cheng et al, 2011;Hamwieh et al, 2011;Liu et al, 2011;Xing et al, 2012).…”
Section: Qtls For Tolerance To Abiotic and Biotic Stresses In Soybeanmentioning
confidence: 99%
“…Hundreds of QTLs for fungal disease resistance have been detected, such as sudden death syndrome, phomopsis seed decay, Sclerotinia stem rot, soybean rust, and Phytopthora root rot. A number of QTLs related to insect and cyst nematode resistances have been identified using various soybean populations under multiple environments (Terry et al, 2000;Xing et al, 2012). Studies on QTL and MAS have also been focused on mitigating negative effects of abiotic stress.…”
Section: Introductionmentioning
confidence: 99%
“…In the event of serious pest damaged years, only veins and petioles have been left on the blades, thereby causing serious yield losses [10]. Relevant research has been reported in regard to the resource excavations of soybeans’ resistance to Lamprosema indicata [10, 11], resistance identification [12, 13], inheritance of the resistance [14, 15] and related gene QTL locations [16, 17]. However, the results of proteomics research which has focused on soybeans’ resistance to Lamprosema indicata has not yet been made available.…”
Section: Introductionmentioning
confidence: 99%